Association of virome dynamics with mosquito species and environmental factors - Qing Liu; Feng Cui; Xiang Liu; Yumei Fu; Wenjing Fang; Xun Kang; Hong Lu; Siping Li; Biao Liu; Wei Guo; Qianfeng Xia; Le Kang; et al. (Microbiome, 2023)
Abstract Background The pathogenic viruses transmitted by mosquitoes cause a variety of animal and human diseases and public health concerns. Virome surveillance is important for the discovery, and control of mosquito-borne pathogenic viruses, as well as early warning systems. Virome composition in mosquitoes is affected by mosquito species, food source, and geographic region. However, the complex associations of virome composition remain largely unknown. Results Here, we profiled the high-depth RNA viromes of 15 species of field-caught adult mosquitoes, especially from Culex, Aedes, Anopheles, and Armigeres in Hainan Island from 2018 to 2020. We detected 57 known and 39 novel viruses belonging to 15 families. We established the associations of the RNA viruses with mosquito species and their foods, indicating the importance of feeding acquisition of RNA viruses in determining virome composition. A large fraction of RNA viruses were persistent in the same mosquito species across the 3 years and different locations, showing the species-specific stability of viromes in Hainan Island. In contrast, the virome compositions of single mosquito species in different geographic regions worldwide are visibly distinct. This is consistent with the differences in food sources of mosquitoes distributed broadly across continents. Conclusions Thus, species-specific viromes in a relatively small area are limited by viral interspecific competition and food sources, whereas the viromes of mosquito species in large geographic regions may be governed by ecological interactions between mosquitoes and local environmental factors. Video Abstract